MOVIE-INDUCED TOURISM AS A POWERFUL TOURISM BRANDING MEDIA (Study Case on “Laskar Pelangi” The Movie) - Mahaning Indrawaty Wijaya; Novi Ahimsa Rosikha (Universitas Airlangga, 2020)
ABSTRACTThe scarcity in natural resources encourage many countries move their focus to manage non-natural resources. Tourism sector is one of potential non-natural resource in Indonesia that needs to be maximized by appropriate media. The fact that number of tourists coming to Bangka Belitung increase until about 1.800% by “Laskar Pelangi” the movie is a good sign that movie can be a tourism branding media to increase desire of audiences to visit the place which is shown. This research examines how “Laskar Pelangi” as a movie-induced tourism can influence audience decision to visit Belitung Island using combination of quantitative and qualitative research. The result shows that Laskar Pelangi is a effective movie-induced tourism since it has both pull and push factors. Understanding this tourism strategy will allow nation to excel economy recovery in the future.Keywords: Movie, Tourism, Economics.